The fairy swarm - Selfors, Suzanne (Selfors, Suzanne <<The>> imaginary veterinary, 2015)
"Ten-year-olds Ben Silverstein and Pearl Petal have had quite a busy summer as apprentices of Dr. Woo, veterinarian for imaginary creatures. When a swarm of sugar fairies escapes into Buttonville, Ben and Pearl must protect the townspeople, keep the fairies safe, and outsmart the dangerous poacher, Maximus Steele"...